Development of an Integrated Watershed Management strategy for Resource Conservation in Balochistan Province of Pakistan - Baloch, Mansoor Ahmed; Tanık, Ayşegül (Elsevier BV, 2008)
The south western province, Balochistan constitutes 44% of Pakistan’s total area. Unsustainable use and management of its natural resources has caused degradation of its water resources, rangelands, forests and soils in croplands. This paper describes major environmental resource management issues in the light of Balochistan Conservation Strategy (BCS) and recommends Integrated Watershed Management (IWM) as an integrated holistic approach towards problem identification and management. The legal, institutional and participatory components for implementation of an IWM plan in Balochistan are also considered. It is found that such an integrated approach indeed has the mandatory options in dealing with the core issues developed and researched in BCS.